Monitoring marine litter on Funchal beaches (Madeira Island): insights for litter management - Bettencourt, Sara (2023)
Marine litter is a complex and multi-dimensional problem, with beach litter surveys being an important cost-effective tool for monitoring and assessing marine litter pollution. In Madeira Island (Portugal, NE Atlantic), a region awarded several times as ‘Europe’s Leading Island Destination’ and with a particular orography, there is a scarce understanding of the situation of marine debris. A two-year monitoring (July 2020 to April 2022) of macro-litter was conducted on two beaches in Funchal, the largest city and capital of the island. The abundance, composition, sources, and pathways of the stranded marine litter were assessed following OSPAR guidelines. During the two years, a total of 14,265 items were recorded. The mean litter density was found to be 0.29 items/m2 and the beaches’ clean index ranged between ‘very clean’ and ‘dirty’. Cigarette butts (30.9%) and plastic objects (30.7%) were the most frequent marine litter items, followed by paper/cardboard (9.2%) and metal items (8.3%). The composition of the litter showed that most of the monitored marine debris has a land-based source, with a strong contribution from smoking-related activities and littering in streams. By characterizing the waste and identifying its source, it was possible to propose integrated management actions at a local level. Outreach and raising awareness campaigns, together with actions to limit single-use plastic items and stimulate a circular economy, could contribute to limit marine litter on the studied island but also in other regions with similar profiles.